Księgarnia i Biblioteka do Czytania Tomasza Szumskiego - Jazdon, Artur (Biblioteka Uniwersytecka w Poznaniu, 2012)
Tomasz Szumski – znany głównie dotychczas w literaturze jako nauczyciel gimnazjalny i autor podręczników – był także właścicielem księgarni i działającej przy niej wypożyczalni książek. Istniały one w latach 1809-1824. Ich założenie należy wiązać ze świadomą chęcią utworzenia placówki stanowiącej przeciwwagę dla niemieckich księgarń, oferującą szerokim kręgom literaturę polską i głównie francuskojęzyczną oraz ze wsparciem uczącej się młodzieży podręcznikami i lekturami. Księgarnia stanowiła dla Szumskiego także dodatkowe źródło dochodu. Szumski starał się o sprzedaż aktualnej produkcji wydawców warszawskich, krakowskich, lwowskich, wrocławskich i wileńskich. Prowadził prenumeratę wielu tytułów gazet i czasopism. Dbał o reklamę, wydając liczne katalogi oraz systematycznie informując o swej działalności na łamach prasy. Księgarnia była placówką małą, w momencie zamknięcia, spowodowanego nakazem administracyjnym, oferowała niecałe 2,5 tysiąca tytułów. Zakupiona została przez niemieckiego księgarza Ernsta S. Mittlera.

Tomasz Szumski, hitherto known in the literature as a secondary school teacher and the author of textbooks, was also the owner of a bookshop and a lending library attached to it. Both were in operation between 1809 and 1824. Their establishment was apparently effected by a deliberate wish to create an establishment that would counterbalance the influence of German bookshops in the town and would offer Polish and foreign literature (mainly French) to as wide circles of readers as possible. Additionally, it was intended to be a bookshop that would provide support to the general public with selling textbooks and assigned reading texts for youths. For Szumski himself, the bookshop was also a source of considerable extra income. Szumski’s intention was to sell as much of the current publishing output from Warsaw, Cracow, Lvov, Wrocław (then Breslau) and Vilna as possible. He also provided subscriptions to a great number of titles of newspapers and periodicals. He did not neglect the marketing issues involved in his line of business and published numerous book catalogues and kept the press well informed about his new acquisitions. In terms of its size, the bookshop was not a big place and, at the time of its forced closure effected by an administrative writ issued by the German authorities, nearly 2,500 titles were on offer. Following its closure it was repossessioned and bought by the German bookseller Ernst S. Mittler.
The bookshop and the public library of Tomasz Szumski
Keywords: Poznań XIX wiek; Poznań-19th c.; życie kulturalne; cultural life; księgarstwo; bookselling; czytelnictwo; readership; Szumski Tomasz